A Multilevel Analysis of Unemployment in Egypt. (29th May 2017) - Bertoni, Eleonora; Ricchiuti, Giorgio
Abstract: Despite its recent economic development, Egypt's employment inequalities among gender and different age cohorts are still an unresolved issue. In this work we apply a Multilevel Generalized Linear Mixed Model to the Egyptian Labor Market Panel Survey 2006 (ELMPS 2006) and 2012 (ELMPS 2012). By exploiting the hierarchical structure of the survey data, we investigate how the interplay between individual characteristics and regional context affects Egyptians' individual probability of being unemployed. Moreover, we attempt to identify if and how these same characteristics have changed between 2006 and 2012 as a consequence of the major changes that re‐shaped Egyptian demographics, labor market structure, and young cohorts' educational achievements.